Effects of Nitrogen in Soybean Seed Quality Definition During Seed-Filling Period - S. Tamagno; E. A. Adee; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2018)
During the seed filling period (SFP), parallel to the seed changes, translocation of assimilates and nutrients takes place from different plant organs to the seed in order to provide sufficient supply for the seed storage components (i.e., starch, oil, and protein) that ultimately will determine the seed quality. There are two processes that define the final seed weight in any crop: 1) the amount of dry mass deposited per unit of time (rate) and 2) the duration of this process from beginning of seed formation to physiological maturity. As seed number is defined, any source limitation during the SFP can affect the final weight and quality of the seeds. This study aims to investigate if nitrogen (N) is limiting potential seed weight and, in consequence, final seed yield as well as the characterization of the deposition of seed components (i.e., oil and protein) that define soybean seed quality among different N conditions and genotypic background.
Keywords: soybean; seed quality; seed filling; late-season N application